LIBRIES: LIBRARY AND INFORMATION SCIENCE RESEARCH E- JOURNAL: A BIBLIOMETRIC ANALYSIS - N. Zafrunnisha (International Journal of Research -GRANTHAALAYAH, 2024)
Present study aims to study the bibliometric analysis of Five years papers published in Library and Information Science Research e- Journal (LIBRIES) during the period from 2018 to 2023. The data was derived from the journal archived volumes through KNIMBUS e-journal database. The study analysed total 1085 citations cited in LIBRIES.